Real-time optimized biofeedback utilizing sport techniques (ROBUST): a study protocol for a randomized controlled trial. Issue 1 (December 2017) - Taylor, Jeffrey; Nguyen, Anh-Dung; Paterno, Mark; Huang, Bin; Ford, Kevin
Abstract Background Anterior cruciate ligament (ACL) injuries in female athletes lead to a variety of short- and long-term physical, financial, and psychosocial ramifications. While dedicated injury prevention training programs have shown promise, ACL injury rates remain high as implementation has not become widespread. Conventional prevention programs use a combination of resistance, plyometric, balance and agility training to improve high-risk biomechanics and reduce the risk of injury. While many of these programs focus on reducing knee abduction load and posture during dynamic activity, targeting hip extensor strength and utilization may be more efficacious, as it is theorized to be an underlying mechanism of injury in adolescent female athletes. Biofeedback training may complement traditional preventive training, but has not been widely studied in connection with ACL injuries. We hypothesize that biofeedback may be needed to maximize the effectiveness of neuromuscular prophylactic interventions, and that hip-focused biofeedback will improve lower extremity biomechanics to a larger extent than knee-focused biofeedback during dynamic sport-specific tasks and long-term movement strategies. Methods This is an assessor-blind, randomized control trial of 150 adolescent competitive female (9–19 years) soccer players. Each participant receives 3x/week neuromuscular preventive training and 1x/week biofeedback, the mode depending on their randomization to one of 3 biofeedback groups (hip-focused, knee-focused, sham). The primary aim is to assess the impact of biofeedback training on knee abduction moments (the primary biomechanical predictor of future ACL injury) during double-leg landings, single-leg landings, and unplanned cutting. Testing will occur immediately before the training intervention, immediately after the training intervention, and 6 months after the training intervention to assess the long-term retention of modified biomechanics. Secondary aims will assess performance changes, including hip and core strength, power, and agility, and the extent to which maturation effects biofeedback efficacy. Discussion The results of the Real-time Optimized Biofeedback Utilizing Sport Techniques (ROBUST) trial will help complement current preventive training and may lead to clinician-friendly methods of biofeedback to incorporate into widespread training practices. Trial registration Date of publication in ClinicalTrials.gov: 20/04/2016. ClinicalTrials.gov Identifier:NCT02754700 .